Identification of active sites in CO oxidation over a Pd/Al2O3 catalyst. Issue 33 (13th August 2019) - Murata, Kazumasa; Eleeda, Eleen; Ohyama, Junya; Yamamoto, Yuta; Arai, Shigeo; Satsuma, Atsushi
Abstract : The active sites of Pd/Al2 O3 catalysts for CO oxidations were identified by investigating the dependence of CO oxidation activities on the surface structure and morphology of Pd nanoparticles. Abstract : The active sites of Pd/Al2 O3 catalysts for CO oxidations were identified by investigating the dependence of CO oxidation activities on the surface structure and morphology of Pd nanoparticles. The maximum catalytic activity was obtained for Pd particles approximately 2 nm in particle size. We performed structural analyses on the Pd surface through infrared (IR) spectroscopy of the adsorbed CO molecules. A positive correlation was obtained between catalytic activity and the fraction of linear CO adsorbed on Pd corner sites and Pd(111) facets, indicating that these sites are highly active for CO oxidation. X-ray absorption fine structure (XAFS) and spherical aberration-corrected scanning transmission electron microscopy (Cs-STEM) measurements demonstrated that Pd nanoparticles less than 2 nm in particle size with amorphous-like structures and Pd particles with large, well-ordered structures favor the formation of a high fraction of corner sites and Pd(111) facets, respectively.